2020
DOI: 10.1002/qua.26143
|View full text |Cite
|
Sign up to set email alerts
|

The effect of silicon doping on the geometrical structures, stability, and electronic and spectral properties of magnesium clusters: DFT study of SiMgn (n = 1‐12) clusters

Abstract: Using the density functional theory (DFT) method at the B3LYP /6−311G (D) level, we studied how silicon doping affects the geometrical structure, stability, and electronic and spectral properties of magnesium clusters. The stable isomers of SiMg n (n = 1‐12) clusters were calculated by searching numerous initial configurations using the CALYPSO program. The geometrical structure optimization shows that most stable SiMg n (n = 3‐12) clusters are three‐dimensional. In addition, geometrical structure growth patte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 49 publications
2
16
0
Order By: Relevance
“…In conclusion, based on the small size of AuMg n-1 or smaller, AuMg n ( n = 2–12) nanoclusters can usually be formed by adsorption of Mg atoms in different directions, and the interesting point is that the direction of adsorption does not have a fixed pattern. Such result is consistent with many existed Mg-based nanoclusters reported ( Li et al, 2017 ; Zeng et al, 2020 , 2021 ; Zhu et al, 2020 ). However, despite the many similarities, the structures of gold-doped Mg nanoclusters have unique properties compared to other Mg-based nanoclusters studies.…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…In conclusion, based on the small size of AuMg n-1 or smaller, AuMg n ( n = 2–12) nanoclusters can usually be formed by adsorption of Mg atoms in different directions, and the interesting point is that the direction of adsorption does not have a fixed pattern. Such result is consistent with many existed Mg-based nanoclusters reported ( Li et al, 2017 ; Zeng et al, 2020 , 2021 ; Zhu et al, 2020 ). However, despite the many similarities, the structures of gold-doped Mg nanoclusters have unique properties compared to other Mg-based nanoclusters studies.…”
Section: Resultssupporting
confidence: 93%
“…However, despite the many similarities, the structures of gold-doped Mg nanoclusters have unique properties compared to other Mg-based nanoclusters studies. For example, the structure of AuMg 3 nanoclusters is 2D planar, while the lowest energy heterostructures of Be ( Zeng et al, 2020 ), Si ( Zhu et al, 2020 ), C, Ge, Sn ( Zeng et al, 2021 ), Zn-doped ( Li et al, 2017 ) Mg nanoclusters of corresponding sizes are all ortho-tetrahedral in shape. Interestingly, although the ground-state structures of AuMg 9 and BeMg 9 ( Zeng et al, 2020 ) look similar, the significant difference between them is that the Au atom locates on the surface of AuMg 9 while the Be atom is absorbed into the inside of BeMg 9 .…”
Section: Resultsmentioning
confidence: 99%
“…Compared with the research results of the local most stable neutral silicon-doped magnesium clusters (Zhu et al, 2020), we can find some interesting conclusions. First of all, whether silicon-doped magnesium clusters are neutral or charged, their local most stable clusters are composed of one silicon and eight magnesium atoms.…”
Section: ±1mentioning
confidence: 62%
“…When the research interest in magnesium silicide sensors is transferred to the nanometer size, it becomes very necessary to use cluster methods to study silicon-doped magnesium clusters. Surprisingly, to our best knowledge, except for our previous work on silicon doped neutral magnesium clusters (Zhu et al, 2020), few studies have been made on silicon-doped charged magnesium alloy nanomaterials. In addition, the physical and chemical properties of the clusters will vary with their size and charge.…”
Section: Introductionmentioning
confidence: 99%
“…Most recently, research found that heteroatom doping is an effective strategy to stabilize geometrical structures or to tune electronic properties. Up to now, based on the different quantum chemistry calculations, studies on metal-doped (Be, Al, Ge, Sn, 3 d and 4 d TM atoms) and nonmetal-doped (B, C, N, O, F and Si) magnesium clusters have harvested many great achievements [ 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 ]. More importantly, based on the CALYPSO structural searching method and DFT, the structures and electronic properties of Be-, Be 2 -, Sr 2 - and Ba 2 -atom-doped differently sized magnesium clusters have been systemically discussed by Zeng’s, Zhao’s and our groups [ 33 , 34 , 35 , 36 , 37 ].…”
Section: Introductionmentioning
confidence: 99%